Efficacy and safety of chinese herbal medicines combined with chemical drugs for alzheimer's disease: A systematic review and meta-analysis - Li Xu; Wen-Jun Chen; Cai-Jun Tian; Yan Zhang; Yan Ma; Tian-Hao Li; Hong-Jie Liu; Zhe Zhang (World Journal of Traditional Chinese Medicine, 2024)
Objective: To evaluate the efficacy and safety of Chinese herbal medicines (CHMs) combined with chemical drugs for the treatment of Alzheimer's disease (AD). Materials and Methods: Databases were searched to retrieve randomized controlled trials (RCTs) of CHMs combined with tacrine, galantamine, rivastigmine, donepezil, or memantine, following strict inclusion and exclusion criteria. Only research papers published in English, Chinese, and Japanese were considered. The primary outcome was the mini-mental state examination (MMSE) score and the secondary outcomes were AD assessment scale cognitive subscale (ADAS-Cog) score and safety evaluation. Meta-analysis was carried out using RevMan 5.3 and subgroup analysis was conducted to identify the sources of heterogeneity. Results: A total of 15 RCTs with 1386 participants were included in this study. Only donepezil was used in the retrieved literature. Meta-analyses showed that the combination of CHMs with donepezil led to significant improvement in the MMSE score (Z = 9.45; P < 0.00001; weighted mean difference [WMD] =2.68, 95% confidence interval [CI]: 2.12–3.24) and a significant decrease in the ADAS-Cog score (Z = 5.53; P < 0.00001; WMD = −3.79; 95% CI: −5.13–−2.44). Safety evaluation demonstrated that these combination treatments relieved adverse events such as insomnia (risk ratio [RR] =0.20, 95% CI: 0.06–0.68; P = 0.01) and hive (RR = 0.10; 95% CI: 0.01–0.73; P = 0.02). Conclusions: The combination of CHMs with a chemical drug like donepezil led to significant improvements in patient cognition as well as a better safety profile when compared to the application of a chemical drug alone.